AKT in cancer: new molecular insights and advances in drug development. (27th June 2016) - Mundi, Prabhjot S.; Sachdev, Jasgit; McCourt, Carolyn; Kalinsky, Kevin
Abstract : The phosphatidylinositol‐3 kinase (PI3K)–AKT pathway is one of the most commonly dysregulated pathways in all of cancer, with somatic mutations, copy number alterations, aberrant epigenetic regulation and increased expression in a number of cancers. The carefully maintained homeostatic balance of cell division and growth on one hand, and programmed cell death on the other, is universally disturbed in tumorigenesis, and downstream effectors of the PI3K–AKT pathway play an important role in this disturbance. With a wide array of downstream effectors involved in cell survival and proliferation, the well‐characterized direct interactions of AKT make it a highly attractive yet elusive target for cancer therapy. Here, we review the salient features of this pathway, evidence of its role in promoting tumorigenesis and recent progress in the development of therapeutic agents that target AKT.